2003
DOI: 10.1007/s00122-003-1474-y
|View full text |Cite
|
Sign up to set email alerts
|

A genetic linkage map of the diplosporous chromosomal region in Taraxacum officinale (common dandelion; Asteraceae)

Abstract: In this study, we mapped the diplosporous chromosomal region in Taraxacum officinale, by using amplified fragment length polymorphism technology (AFLP) in 73 plants from a segregating population. Taraxacum serves as a model system to investigate the genetics, ecology, and evolution of apomixis. The genus includes sexual diploid as well as apomictic polyploid, mostly triploid, plants. Apomictic Taraxacum is diplosporous, parthenogenetic, and has autonomous endosperm formation. Previous studies have indicated th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
60
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(66 citation statements)
references
References 38 publications
5
60
1
Order By: Relevance
“…The effect of the environment on male sterility, especially the impact of day length and temperature, was reported in Cajanus cajan, where high temperatures and longer days maintained male-sterility, while shorter days and lower temperature induced male fertility (Saxena et al 2010). Similarly, in some individuals of the male-sterile diploid dandelions, the production of pollen depended on the temperature (Van der Hulst et al 2004). In the light of these findings, it can be assumed that the presence of pollen observed in the investigated individuals of male-sterile T. belorussicum from Poland is a sign of such intraspecific variation in pollen production, which may be affected by environmental factors.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…The effect of the environment on male sterility, especially the impact of day length and temperature, was reported in Cajanus cajan, where high temperatures and longer days maintained male-sterility, while shorter days and lower temperature induced male fertility (Saxena et al 2010). Similarly, in some individuals of the male-sterile diploid dandelions, the production of pollen depended on the temperature (Van der Hulst et al 2004). In the light of these findings, it can be assumed that the presence of pollen observed in the investigated individuals of male-sterile T. belorussicum from Poland is a sign of such intraspecific variation in pollen production, which may be affected by environmental factors.…”
Section: Discussionmentioning
confidence: 98%
“…Maynard Smith (1978) suggested that apomicts producing pollen are phylogenetically relatively young to have accumulated the necessary mutations that cause male sterility. However, male sterility has been found in both diploid sexual and apomictic dandelions representing numerous sections (Van Soest 1965;Richards 1970;Małecka 1971b; Van der Hulst et al 2004;Meirmans et al 2006). Pollen production is linked to a significant reproductive cost, thus, the male sterility in apomicts can be considered as a reallocation of resources from male function to increase female fitness.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…If the hybridisation theory is correct, then the genomic regions controlling the initiation of apomixis might simply reflect key regulators of the sexual pathway that are mis-expressed in time and space. This may be an important point to consider as mapping and mutagenesis approaches in Pennisetum, Hieracium and Taraxacum and other apomictic species approach the core regions controlling apomixis in these plants (Vijverberg et al 2004;Akiyama et al 2005;Catanach et al 2006).…”
Section: Interspecific Hybridisation May Lead To the Initiation Of Apmentioning
confidence: 99%